Ultralow energy calibration of LUX detector using $^{127}$Xe electron capture - LUX collaboration (93 authors) (2017)
We report an absolute calibration of the ionization yields (Qy) and fluctuations for electronic recoil events in liquid xenon at discrete energies between 186 eV and 33.2 keV. The average electric field applied across the liquid xenon target is 180  V/cm. The data are obtained using low energy Xe127 electron capture decay events from the 95.0-day first run from LUX (WS2013) in search of weakly interacting massive particles. The sequence of gamma-ray and x-ray cascades associated with I127 deexcitations produces clearly identified two-vertex events in the LUX detector. We observe the K-(binding energy, 33.2 keV), L-(5.2 keV), M-(1.1 keV), and N-(186 eV) shell cascade events and verify that the relative ratio of observed events for each shell agrees with calculations. The N-shell cascade analysis includes single extracted electron (SE) events and represents the lowest-energy electronic recoil in situ measurements that have been explored in liquid xenon.